2023
DOI: 10.21037/acs-2022-urats-169
|View full text |Cite
|
Sign up to set email alerts
|

Uniportal robotic versus thoracoscopic assisted surgery: a propensity score-matched analysis of the initial 100 cases

Abstract: Background: Minimally invasive surgery (MIS) is becoming the standard of care for anatomic lung resections. The advantages of the uniportal approach compared to the conventional multiple incision approach, multiportal video-assisted thoracic surgery (mVATS) and multiportal robotic-assisted thoracic surgery (mRATS), have been previously described. However, no research studies comparing early outcomes between uniportal video-assisted thoracic surgery (uVATS) and uniportal robotic-assisted thoracic surgery (uRATS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
(38 reference statements)
0
10
0
Order By: Relevance
“…The median operative time was statistically lower in URATS group (136 vs. 150 min) and the median length of stay was significantly shorter in the URATS group (4 vs. 5 days). Rate of complications and 30-day mortality was low in both groups ( 20 ).…”
Section: Commentsmentioning
confidence: 89%
“…The median operative time was statistically lower in URATS group (136 vs. 150 min) and the median length of stay was significantly shorter in the URATS group (4 vs. 5 days). Rate of complications and 30-day mortality was low in both groups ( 20 ).…”
Section: Commentsmentioning
confidence: 89%
“…A total of 137 studies on the application of u-RATS were identified for inclusion, with 12 progressing to inclusion (5 cohort series, 7 case reports) (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The cohort series are presented in Table 3.…”
Section: Study Characteristics and Baseline Demographic Data (See Tab...mentioning
confidence: 99%
“…All 5 included cohort studies (7,8,11,14,15) were deemed to be of low risk of bias, with the primary concern being the lack of control arms and potential for selection bias given strict selection criteria of the patients for the series.…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Paradela and colleagues compared U‐RATS with U‐VATS in a group of 200 patients undergoing anatomic lung resections 74 . The authors discovered that U‐VATS was associated with higher rates of intraoperative bleeding (5% vs. 0%) and length of chest tube duration (3.9 days vs. 2.5 days).…”
Section: Evolution Of Uniportal Surgerymentioning
confidence: 99%